2017
DOI: 10.1038/nrg.2017.8
|View full text |Cite
|
Sign up to set email alerts
|

Functional variomics and network perturbation: connecting genotype to phenotype in cancer

Abstract: Proteins interact with other macromolecules in complex cellular networks for signal transduction and biological function. In cancer, genetic aberrations have been traditionally thought to disrupt the entire gene function. It has been increasingly appreciated that each mutation of a gene could have a subtle but unique effect on protein function or network rewiring, contributing to diverse phenotypic consequences across cancer patient populations. In this Review, we discuss the current understanding of cancer ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
79
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 82 publications
(79 citation statements)
references
References 169 publications
(182 reference statements)
0
79
0
Order By: Relevance
“…In principle, somatic mutations may disrupt the overall structure of the corresponding protein, or alternatively exert specific effects on particular molecular interactions . To evaluate whether and how cancer mutations affect the binding of RBPs to their targets, we systematically explored the localization of somatic mutations on the three‐dimensional protein structures of RBPs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In principle, somatic mutations may disrupt the overall structure of the corresponding protein, or alternatively exert specific effects on particular molecular interactions . To evaluate whether and how cancer mutations affect the binding of RBPs to their targets, we systematically explored the localization of somatic mutations on the three‐dimensional protein structures of RBPs.…”
Section: Resultsmentioning
confidence: 99%
“…Most previous studies modeled genotype–phenotype relationships based on the assumption that driver mutations lead to complete loss of protein function through radical changes, such as protein instability or misfolding. However, it has been increasingly appreciated that many driver mutations could act to perturb molecular interactions important for cellular functions . We previously reported that a considerable fraction of driver disease mutations caused protein–protein interaction‐specific or “edgetic” perturbations .…”
mentioning
confidence: 99%
“…Analysis of the genetic determinants of cancer and other diseases, clearly shows that gene loss-of-function and gene amplification or gain-of-function are equally important determinants of disease progression [1618]. Several different genome-wide reagent sets are available for the systematic analysis of genetic interactions involving overexpression alleles in yeast.…”
Section: Mapping Digenic Interactions Using Gain-of-function Allelesmentioning
confidence: 99%
“…However, few noncoding cancer‐associated mutations have been studied as of date. TFs often bind to noncoding regulatory DNAs to mediate transcription, therefore protein–DNA assays such as chromatin immunoprecipitation sequencing (ChIP‐seq), yeast one‐hybrid, and protein‐binding microarray can be used to assess the function of noncoding mutations . Moreover, in vivo assay of noncoding mutational effect is needed to gain better insight into carcinogenesis.…”
mentioning
confidence: 99%
“…Moreover, in vivo assay of noncoding mutational effect is needed to gain better insight into carcinogenesis. Recent advances in the CRISPR technology enables genome‐wide screens to evaluate functional consequences of noncoding regions in vivo . Systematic experimental and analytical platforms will be insightful in identifying disease‐causing mutations and uncovering patient mutation‐specific disease mechanisms in liver cancer.…”
mentioning
confidence: 99%